The Constantinos Karamanlis Institute for Democracy Yearbook 2010 - Arvanitopoulos, Constantine.; Botsiou, Konstantina E. (The Constantinos Karamanlis Institute for Democracy Yearbook Series,, 2010)
2010 marks a turning point for international politics. The impact of the global crisis is reflected in the readiness of both national governments and international organisations to rebuild relations between state and market within a safer regulatory framework. New models of development gained ground during the crisis: investments in new energy technologies, medical research, education, security and employment. In Europe, novel ideas interact with major institutional changes put into effect by the Lisbon Treaty. A wide range of policies, from the field of European security to the problems of migration and from EU enlargement to Euro-American cooperation, are affected by the changes on all these levels. The Constantinos Karamanlis Institute for Democracy Yearbook 2010 addresses vital aspects of the European and international agenda, bringing together prominent scholars and policymakers from a variety of national backgrounds. This special thematic issue on recent history illustrates the long-term interplay between Greek politics, on the one hand, and Europeanisation, liberalism and historical memory, on the other hand.